One hundred Saturdays : Stella Levi and the search for a lost world - Frank, Michael, 1959 June 2- (Avid Reader Press, 2022)
"The remarkable story of ninety-nine-year-old Stella Levi whose conversations with the writer Michael Frank over the course of six years bring to life the vibrant world of Jewish Rhodes, the deportation to Auschwitz that extinguished ninety percent of her community, and the resilience and wisdom of the woman who lived to tell the tale"--